Evaluating the performance of a rapid antigen test for the detection of influenza virus in clinical specimens from children in Cameroon. Issue 2 (24th November 2013) - Kenmoe, Sebastien; Tchendjou, Patrice; Moyo Tetang, Suzie; Mossus, Tatiana; Njankouo Ripa, Mohammed; Guillet, Marlène; Kfutwah, Anfumbom; Njouom, Richard
<x xml:space="preserve">Abstract</x> The performance of SD Bioline rapid antigen test (RAT) was evaluated using real‐time reverse transcription polymerase chain reaction (rRT‐PCR) as gold standard. A total of 718 nasal swabs, including 102 rRT‐PCR positive and 616 rRT‐PCR negative swabs, were tested. RAT demonstrates a sensitivity of 29·4% with a specificity of 100%. The positivity rate of RAT was highly associated with lower cycle threshold (Ct) values (P < 0·0001). The excellent specificity of the RAT allowed for the rapid identification of influenza cases. However, negative results should be verified by rRT‐PCR test because of limitations observed in sensitivity.